The topic of asset science An inductive and analytical study to show the opinions of scholars on the subject of the science of origins, both in denial and in affirmation - Ibrahim Salman Qassem Hashem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Our research, marked by the subject of the science of origins, deals with the meaning of the origin linguistically and idiomatically, and the reality of the subject, as well as the necessity of proving the subject for knowledge or not, and also deals with the evidence of those who say that there is a subject for every science, and the research is also exposed to a statement of evidence for those who say that it is not necessary to prove the subject for some sciences and its impossibility, as The research deals with a paperweight diagnosing the subject of the science of origins, which some scholars consider that the subject of the science of origins is a common evidence in jurisprudential reasoning in particular. With an introduction, conclusion and index of sources.